Practical training and the audit expectations gap: The case of accounting undergraduates of Universiti Utara Malaysia - Md. Ali, Azham; Lee, Teck Heang; Mohamad, Rosli; Mohamad Yusof, Nor Zalina; Ojo, Marianne (Social Science Electronic Publishing, 2007)
The accounting profession has long faced the issue of an audit expectation gap; being the gap between the quality of the profession’s performance, its objectives and results, and that which the society expects.The profession believes that the gap could be reduced over time through education.Studies have been carried out overseas and in Malaysia to determine the effect of education in narrowing the audit expectation gap. Extending the knowledge acquired, this paper investigates whether academic internship programs could reduce the audit expectation gap in Malaysia.Using a pre-post method, the research instrument adapted from Ferguson et al.(2000) is administered to the Universiti Utara Malaysia’s accounting students at the beginning and end of their internship program.The results show there is a significant change in perceptions among students after the internship program. However, changes in perceptions do not warrant an internship program as a means of reducing the audit expectation gap as misperceptions are still found among respondents on issues of auditing after the completion of the internship program. Nevertheless, an internship program can still be used to complement audit education in a university as it is an ideal way to expose students to professional issues and enables them to have a better insight of the actual performance and duties of auditors.